Discovery of Novel Entomopathogenic Fungi for Mosquito-Borne Disease Control - Accoti, Anastasia; Engdahl, Cecilia Springer; Dimopoulos, George (Frontiers in Fungal Biology, 2021)
The increased application of chemical control programs has led to the emergence and spread of insecticide resistance in mosquitoes. Novel environmentally safe control strategies are currently needed for the control of disease vectors. The use of entomopathogenic fungi could be a suitable alternative to chemical insecticides. Currently, Beauveria spp. and Metarhizium spp. are the most widely used entomopathogenic fungi for mosquito control, but increasing the arsenal with additional fungi is necessary to mitigate the emergence of resistance. Entomopathogenic fungi are distributed in a wide range of habitats. We have performed a comprehensive screen for candidate mosquitocidal fungi from diverse outdoor environments in Maryland and Puerto Rico. An initial screening of 22 fungi involving exposure of adult An. gambiae to 2-weeks-old fungal cultures identified five potent pathogenic fungi, one of which is unidentified and the remaining four belonging to the three genera Galactomyces sp., Isaria sp., and Mucor sp. These fungi where then screened against Ae. aegypti, revealing Isaria sp. as a potent mosquito killer. The entomopathogenic effects were confirmed through spore-dipping assays. We also probed further into the killing mechanisms of these fungi and investigated whether the mosquitocidal activities were the result of potential toxic fungus-produced metabolites. Preliminary assays involving the exposure of mosquitoes to sterile filtered fungal liquid cultures showed that Galactomyces sp., Isaria sp. and the unidentified isolate 1 were the strongest producers of factors showing lethality against An. gambiae. We have identified five fungi that was pathogenic for An. gambiae and one for Ae. aegypti, among these fungi, four of them (two strains of Galactomyces sp., Mucor sp., and the unidentified isolate) have never previously been described as lethal to insects. Further characterization of these entomopathogenic fungi and their metabolites needs to be done to confirm their potential use in biologic control against mosquitoes.